Designing an innovative method to determine the degree and level of sprained wrist ligament injury in athletes with wrist injuries - Atshan Abdalreda , Ahmed; Jasim Swadi , Ali; Mohammad Radhi , Maher (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
This study aimed to develop a specialized method for quantifying the severity and extent of sprained ligaments in the wrist joint of injured athletes, while also assessing the level of pain experienced by athletes with such injuries. The researchers used the experimental method to suit the nature of the problem in a one-group approach. The study targeted athletes with wrist sprain ligament injuries in Dhi Qar Governorate, which included handball, gymnastics, track and field, and basketball. The research community comprised athletes with wrist ligament sprains in Dhi Qar Governorate, totalling six athletes, representing 100% of the sample. The researchers used the following means and tools: the personal interview, tests and measurements, a device manufactured to measure the level of the wrist joint ligament injury (measured in degrees). The values of the arithmetic mean and standard deviation of the measurement of flexion down and flexion up showed that there is a great potential for this manufactured device to measure the degree of injury of the joint ligaments among athletes. This device effectively distinguishes between injuries resulting from flexion downward and upward movements. Moreover, the method devised by the researchers can be relied upon to predict future occurrences of sports injuries within the joint’s range of motion.